The Emergence of the Socioeconomic Gradient in Women's Marriage Outcomes - Olivetti, Claudia; Paserman, M. Daniele; Salisbury, Laura; Weber, E. Anna (The Review of Economics and Statistics, 2024)
Abstract We present new findings about the relationship between marriage and socioeconomic background in the United States in the late 19th and early 20th centuries. Imputing socioeconomic status of family of origin from first names, we document a socioeconomic gradient for women in the probability of marriage and the socioeconomic status of husbands, which widens over this period. Regional divergence in occupational structure explains half of the divergence in the probability of marriage, and most of the increase in marital sorting. Urbanization and the associated improvement in women's labor market opportunities drive most of these differences.